An Analytical Study Of The Role Of Media In Ghafar Shahzad’s Novel "Karol Ghati" - Dr. Robina Parveen , Arshad Mahmood Haadi , Saqlain Ahmad Khan , Dr. Aqsa Naseem Sindhu , Syed Azwar Abbas (Migration Letters, 2024)
Ghafar Shahzad is the glory of the literary circles. In the last two years, two of his novels "Mukli Mein Murg" and "Karol Ghati" have been published. "Karol Ghati" has been published and has received great acclaim in the literary circles, so far countless articles have been written on this novel and there is no doubt that this novel is worthy of it. Ghafar Shahzad has written the novel "Karol Ghati" on a sad incident that happened in the suburbs of Lahore some year ago in which a woman was raped in front of her children. After a month and a h[1]alf, the main accused was arrested. Ghafar Shehzad has written this novel based on this incident and it is well written. This novel has been written according to today’s modern requirements, which is a great addition to Urdu literature, today is the era of electronic media, which has now gone from mainstream TV channels and radio to social media, which is called social media. Written in the context, it is a wonderful experience in Urdu literature about media character.